(untitled) (CIPEEX, 2024)
THIS STUDY AIMS TO VERIFY THE CORRELATION BETWEEN EVIDENCE THEORY AND TECHNOLOGY AS A SOURCE OF ILLICIT EVIDENCE IN THE CONTEXT OF THE LEGAL SYSTEM. COURTS PLAY A FUNDAMENTAL ROLE IN EVALUATING THE LEGALITY OF THIS TECHNOLOGICAL EVIDENCE, ENSURING A BALANCE BETWEEN THE SEARCH FOR TRUTH AND THE PROTECTION OF FUNDAMENTAL RIGHTS. WE CONCLUDED THAT THE CORRELATION BETWEEN PROOF THEORY AND TECHNOLOGY IS A COMPLEX MATTER AND CONSTANTLY EVOLVING. TO ENSURE JUSTICE IN THE CONTEXT OF TECHNOLOGY AS A SOURCE OF EVIDENCE, IT IS ESSENTIAL THAT THE LEGAL SYSTEM ADAPTS AND ESTABLISHES CLEAR LIMITS FOR THE OBTAINING AND ADMISSIBILITY OF TECHNOLOGICAL EVIDENCE. THIS WILL ENSURE THAT THE SEARCH FOR TRUTH OCCURS WITHIN LEGAL PARAMETERS, PROTECTING INDIVIDUAL RIGHTS AND MAINTAINING THE INTEGRITY OF THE JUDICIAL PROCESS IN A SOCIETY UNDERGOING CONSTANT TECHNOLOGICAL TRANSFORMATION. THE RESEARCH WAS BASED ON EXPLORATORY STUDIES AND QUALITATIVE ANALYSIS, WHICH, IN TURN, WAS BASED ON DOCUMENTARY SOURCES, INCLUDING JURISPRUDENCE, COURT DECISIONS, CASE STUDIES, LEGAL DOCTRINES, EXPERT REPORTS AND RELEVANT CASE STUDIES RELATED TO EVIDENCE THEORY AND TECHNOLOGY AS A SOURCE OF EVIDENCE ILLICIT. WE FOUND THAT THE INTEGRATION OF TECHNOLOGY IN INVESTIGATIONS AND LEGAL PROCEEDINGS PRESENTS SIGNIFICANT CHALLENGES IN RELATION TO THE PRESERVATION OF INDIVIDUAL RIGHTS AND THE ADMISSIBILITY OF THE EVIDENCE OBTAINED. THE USE OF TECHNOLOGIES SUCH AS ELECTRONIC SURVEILLANCE, INTERCEPTION OF COMMUNICATIONS AND OBTAINING DIGITAL DATA RAISES QUESTIONS ABOUT PRIVACY AND LEGALITY.